Antioxidant soy peptide can inhibit xanthine oxidase activity and improve LO2 cell damage. (April 2023) - Dong, Yifei; Sun, Na; Ge, Qi; Lv, Renzhi; Lin, Songyi
Abstract: In this study, SHECN (Ser-His-Glu-Cys-Asn) and SHCMN (Ser-His-Cys-Met-Asn) soybean peptides were used as the research objects to investigate their antioxidant activities and XO (xanthine oxidase) activity reduction effects. The results show that SHECN and SHCMN have strong antioxidant activities, and at the same time protect the oxidative stress damage caused by HUA (hyperuricemia). They can quench XO, change the secondary structure of XO, and reduce its activity, which leads to the reduction of UA (uric acid) levels. Molecular docking demonstrated soybean peptides could bind to XO target proteins, respectively. In this study, SHECN and SHCMN were obtained from soybean peptides. Based on the data, soy peptides may be an attractive natural ingredient for the development of novel functional foods that inhibit XO activity. Graphical abstract: Image 1 Highlights: This is the first report to investigate the xanthine oxidase inhibitory activity of SHECN and SHCMN. SHECN and SHCMN regulate XO activity in hyperuricemic cell model. SHECN and SHCMN improve oxidative stress damage and mitochondrial membrane damage and enhance cell viability. SHECN and SHCMN inhibit the reaction with the substrate xanthine by altering the structure of xanthine oxidase. Prediction of the interaction between peptides and key enzymes in uric acid synthesis by molecular docking simulation.